Generation of functional dendritic cells for potential use in the treatment of acute lymphoblastic leukemia - Pospísilová, Dagmar; Borovicková, Jirina; Poloucková, Andrea; Spísek, Radek; Sedivá, Anna; Hrusák, Ondrej; Starý, Jan; Bartůnková, Jirina (Cancer immunology, immunotherapy, 2002)
Immunotherapy of malignant diseases mediated by dendritic cells (DC) pulsed with tumor antigens ex vivo is a promising new tool in the individual treatment of malignant diseases. The present study focuses on the problem of how to optimize in vitro culture conditions and induce the maturation of DC with the capacity to induce antitumor immunity toward leukemic cells. DC were generated from peripheral mononuclear cells by co-cultivation with granulocyte/macrophage-colony stimulating factor (GM-CSF) and interleukin-4 (IL-4). Tumor antigens were added for 2 h after 7 days in culture. Irradiated leukemic blasts, blast lysate, apoptotic cells from the Jurkat cell line (T ALL) and their lysate were used in various concentrations for antigen pulsing. Harvested DC were phenotyped by flow cytometry, and viability was assessed using trypan blue exclusion (Annexin test). After the cells had been pulsed with tumor antigens and co-cultured with autologous lymphocytes, the production of interferon-gamma (IFN-gamma) and IL-12 was analyzed, and lymphocyte proliferative response and cytotoxicity against the target tumor cell line were assessed. The cultivation of monocytes under the described conditions led to the expression of surface markers typical of DC (i.e. CD83, CD86, HLA-DR, CD11c and CD40). Pulsation by antigens from leukemic cells further increased the cell populations expressing these markers. Antigen pulsation decreased the viability of generated DC depending on the increase in concentration of tumor antigens. Pulsed DC-lymphocyte interaction increased the proliferative response of lymphocytes and IFN-gamma production depending on the type of tumor antigens used for pulsation. The highest proliferative response was detected with DC pulsed with Jurkat cell-line lysate. Similarly to the proliferation assay, cytotoxic testing showed the highest efficiency of DC pulsed with Jurkat cell-line lysate in killing the target malignant cells. Our results show that an appropriate antigen concentration used for DC pulsing is one of the crucial factors in an effective treatment strategy, as high concentrations of tumor antigens induce apoptosis of DC, thereby rendering them non-functional. Under optimal conditions, pulsation by lysate from leukemic blasts induced the maturation of DC and led to an increase in the proliferation of autologous lymphocytes, to the production of Th1-cytokines and to the induction of cytotoxicity toward the leukemic cell line. These results are encouraging for the possible application of pulsed DC in the therapy of acute lymphoblastic leukemia.
Keywords: Interleukin-12; viabilita buněk; Interferon-gamma; antigeny nádorové; Lymphocyte Activation; Cancer Vaccines; Cell Survival; interferon gama; dendritické buňky; akutní lymfatická leukemie; cytotoxicita imunologická; aktivace lymfocytů; Immunotherapy; interleukin-12; lidé; Immunophenotyping; Humans; Antigens, Neoplasm; imunoterapie; protinádorové vakcíny; Dendritic Cells; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Cytotoxicity, Immunologic; imunofenotypizace